2016
DOI: 10.1021/jacs.6b11739
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Entry into the Illicium Sesquiterpenes: Enantiospecific Synthesis of (+)-Pseudoanisatin

Abstract: Illicium sesquiterpenes have been the subject of numerous synthetic efforts due to their ornate and highly oxidized structures as well as significant biological activities. Herein we report the first chemical synthesis of (+)-pseudoanisatin from the abundant feedstock chemical cedrol (~$50 USD/kg) in 12-steps using extensive site-selective C(sp3)–H bond functionalization. Significantly, this work represents a novel oxidative strategic template for future approaches to these natural products and their analogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
49
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 58 publications
(29 reference statements)
1
49
0
Order By: Relevance
“…This procedure delivered 7 in 67% yield and on 120 mmol scale. 11 Diverging from past work, in which an olefin oxidative cleavage reaction was used to generate a keto acid, 10 we found that 7 could be converted into ketone 8 directly via a hydroboration/double oxidation sequence (BH 3 ·THF/CrO 3 ·2pyr.). The use of Collin’s reagent avoided hydrolysis of the acetate protecting group as compared to many other oxidants examined.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…This procedure delivered 7 in 67% yield and on 120 mmol scale. 11 Diverging from past work, in which an olefin oxidative cleavage reaction was used to generate a keto acid, 10 we found that 7 could be converted into ketone 8 directly via a hydroboration/double oxidation sequence (BH 3 ·THF/CrO 3 ·2pyr.). The use of Collin’s reagent avoided hydrolysis of the acetate protecting group as compared to many other oxidants examined.…”
mentioning
confidence: 84%
“…10 During our work, iron- and radical-mediated oxidations of the cedrol C-4 methine (shown in green) and C-14 methyl positions (shown in blue) respectively were employed as key steps. In extending this strategy to the more highly oxidized majucinoids, such as 1 and 2 , it is also necessary to oxidize all the C–H bonds of the C-12 methyl group and the indicated C–H bond of the C-10 methylene (both shown in magenta, seco -prezizaane numbering).…”
mentioning
confidence: 99%
“…More recently, during a synthesis of Me‐jasmonate via the α ‐halogenation/dehydrohalogenation of 2‐(pent‐2‐yn‐1‐yl)cyclopentan‐1‐one, we encountered the additional problem of endo/exo ‐cyclic regioselectivity during the dehydrohalogenation, and could only minimize this drawback under neutral conditions . We thus similarly applied the Kochi 's methodology to 2a ,, and, to our delight, we obtained directly and cleanly, in a one pot, DHH 1a . This domino reaction, constitutes the shortest synthesis of 1a , thus avoiding trans ‐ Hedione ® 6a as a starting material for either halogenation/dehydrohalogenation,, or enol acetate formation/epoxidation/rearrangement, or HIO 3 oxidation,, , as key intermediate for the final hydrogenation towards the olfactively more appreciated cis ‐ Hedione ® 6b , or its even more powerful enantiomer (+)‐(1 R ,2 S )‐ cis ‐ 6b , named Paradisone ® ,…”
Section: Introductionmentioning
confidence: 99%
“…2 More recently, during a synthesis of Me-jasmonate via the a-halogenation/dehydrohalogenation of 2-(pent-2-yn-1-yl)cyclopentan-1-one, we encountered the additional problem of endo/exo-cyclic regioselectivity during the dehydrohalogenation, and could only minimize this drawback under neutral conditions. [17] We thus similarly applied the Kochi's methodology to 2a, [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33], 3 and, to our delight, we obtained directly and cleanly, in a one pot, DHH 1a. This domino reaction, constitutes the shortest synthesis of 1a, thus avoiding trans-Hedione â 6a as a starting material for either halogenation/dehydrohalogenation, [31][33] [34],4 1 For the diethyl 2-(3-oxo-2-pentylcyclopentyl)malonate analogue, see.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation